Mycobacterium molecular microbiology - Parish, Tanya (Horizon Bioscience, 2005)
Horizon Scientific Press titles focus on high-level microbiology and molecular biology topics. Written by internationally renowned and highly respected leaders in the field, they comprise review manuals, practical manuals, and reference texts for research scientists, bioscience professionals and graduate students.